Representasi Anak Sulung sebagai Pilar Keluarga di Film Bila Esok Ibu Tiada - Gabriella Shalisha Pratikna; Lusia Savitri Setyo Utami (Koneksi, 2026)
The family is the primary space for shaping social roles, including the position of the firstborn, which in many Indonesian cultures is often understood as the bearer of the greatest responsibility. Representations of this role frequently appear in mass media, including films. This study aims to examine how the firstborn as the pillar of the family is represented in the film Bila Esok Ibu Tiada using Roland Barthes’ semiotic analysis. The research employs a descriptive qualitative approach with Barthes’ semiotic textual analysis. The concepts and theories used include film as a mass communication medium, representation, and social roles. The findings show that the film represents the firstborn as a central figure who holds leadership responsibilities, makes decisions, and maintains family stability. The film also portrays the firstborn’s sacrifices as a form of devotion aligned with Indonesian cultural values that place collective interests above individual needs. In addition, the film reveals unequal distribution of roles and the social and emotional pressures that are often overlooked. Thus, these representations reflect dominant cultural constructions within Indonesian society rather than universal social realities.     Keluarga merupakan ruang utama dalam pembentukan peran sosial, termasuk posisi anak sulung yang dalam sebagian budaya Indonesia sering dipahami sebagai pemegang tanggung jawab terbesar. Representasi mengenai peran tersebut beberapa kali muncul dalam media massa, salah satunya film. Penelitian ini bertujuan mengetahui bagaimana anak sulung sebagai pilar keluarga direpresentasikan dalam film Bila Esok Ibu Tiada dengan analisis semiotika Roland Barthes. Penelitian menggunakan pendekatan deskriptif kualitatif dengan metode analisis teks yaitu semiotika Roland Barthes. Konsep dan teori yang digunakan adalah film sebagai media massa, representasi, dan peran sosial. Hasil penelitian menunjukkan bahwa film merepresentasikan anak sulung sebagai figur sentral yang memegang peran kepemimpinan, pengambil keputusan, dan penjaga stabilitas keluarga. Film juga merepresentasikan pengorbanan anak sulung sebagai bentuk pengabdian yang selaras dengan nilai budaya Indonesia yang menempatkan kepentingan bersama di atas kepentingan pribadi. Selain itu, tampak ketidakadilan pembagian peran serta tekanan sosial dan emosional yang sering tidak disadari. Dengan demikian, representasi tersebut mencerminkan konstruksi budaya yang dominan di masyarakat Indonesia, daripada realitas sosial secara keseluruhan.